Mechanical properties and numerical simulation analysis on large deformation of Jiangluling Carbonaceous Shale Tunnel - Cao, Peng; Hu, Xuebing; Liu, Enlong; Guo, Hongyan (Frontiers in Earth Science, 2023)
Taking the Jiangluling Carbonaceous Shale Tunnel as an example, this study aims to investigate the mechanism of large deformation and design construction technology of carbonaceous shale tunnels. Using theoretical analysis and comparative analysis of numerical simulation and field measured data, the mechanism, mechanical properties, and causes of large squeezing deformation of the Jiangluling Tunnel were analyzed. The study results are as follows: 1) Six failure modes of the support structure can be generated due to the large deformation of the surrounding rocks during the construction of Jiangluling Carbonaceous Shale Tunnel; 2) The causes of large deformation during the construction can be divided into internal and external causes; 3) The deformation degree of the surrounding rock of Jiangluling Carbonaceous Shale Tunnel increases with the burial depth in an approximately linear manner. Under deep-buried conditions, horizontal convergence is more severe than vault settlement in carbonaceous shale tunnels; 4) The deformation of the construction cavern of the Jiangluling Carbonaceous Shale Tunnel typically includes the displacement before tunnel face excavation, tunnel face deformation, and deformation behind the tunnel face. The advance displacement accounts for 30.73% of the total displacement. The influence range of advance displacement is 1-1.2D in front of the tunnel face. These results can provide a reference for the design and construction of carbonaceous shale tunnels.